The upgrade of the PreProcessor system of the ATLAS level-1 calorimeter trigger - Andrei, George Victor; Hanke, Paul; Jongmanns, Jan; Khomich, Andrei; Meier, Karlheinz; Schmitt, Klaus; Schultz-Coulon, Hans-Christian; Stamen, Rainer; Stock, Peter; Wessels, Martin (Journal of Instrumentation, 2012)
The ATLAS Level-1 Calorimeter Trigger is a pipelined system to identify high- p T objects and to build energy sums within a fixed latency of 2 μs. It consists of a PreProcessor, which conditions and digitises analogue calorimeter signals, and two object-finding processors. The PreProcessor's tasks are implemented on a Multi-Chip Module, holding ADCs, time-adjustment and digital processing ASICs, and LVDS serialisers. A pin-compatible substitute, based on today's technology, like dual-channel ADCs and FPGAs, has been built to improve the BCID and pedestal subtraction algorithms. Test results with the first prototype are presented.